1994
DOI: 10.1002/hrdq.3920050107
|View full text |Cite
|
Sign up to set email alerts
|

A review of cross‐cultural research on human resource development

Abstract: Organizations increasingly operate within a global context. Likewise, human resource developers are challenged to examine the transferability of their dforts. Our analysisfocuses on emerging testimony that marks and sustains the cultural sensitivity of our work. Empirical study between 1982 and 1992 was reviewed. Furthermore, we acknowledge the systemic importance of our craft by selectively reporting research in management and organizational behavior that affects cross-national dgerences in the purpose and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 74 publications
0
34
0
1
Order By: Relevance
“…Meanwhile, some researchers have viewed certain leadership styles as universal and effective in all situations (Avolio and Bass, 1995;Bass, 1999), while others have suggested that leadership styles should be examined within various situational and cultural contexts (Easterman and Pawar, 1997;Wofford et al, 2001;Avolio et al, 2003;House et al, 2004;Dickson et al, 2003). Yet, studies investigating the impact of societal culture on managerial behaviors and leadership styles in developing societies are still rare, despite repeated calls for this type of research to keep pace with the rapidly developing international and multi-cultural organizational environments (Hansen and Brooks, 1994;Peterson, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, some researchers have viewed certain leadership styles as universal and effective in all situations (Avolio and Bass, 1995;Bass, 1999), while others have suggested that leadership styles should be examined within various situational and cultural contexts (Easterman and Pawar, 1997;Wofford et al, 2001;Avolio et al, 2003;House et al, 2004;Dickson et al, 2003). Yet, studies investigating the impact of societal culture on managerial behaviors and leadership styles in developing societies are still rare, despite repeated calls for this type of research to keep pace with the rapidly developing international and multi-cultural organizational environments (Hansen and Brooks, 1994;Peterson, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of international human resource development (IHRD), this lack is felt especially keenly (see Hansen and Brooks, 1994;McLean, 1991; Peterson, 19971, but it is also felt in the related fields of human resource management (see Brewster, Tregaskis, Hegewich, and Mayne, 1996) and organizational behavior (see Lytle and…”
mentioning
confidence: 99%
“…Scholars have continuously discovered that HRD in different countries confronts different problems. Social and cultural factors in each country influence learning styles and performance recognition and therefore lead to discrepancies in HRD tasks and development patterns (Hansen & Brooks, 1994). Thus, it is also crucial for Chinese scholars to develop a relevant HRD framework based on the Chinese culture and learning style.…”
Section: The Weaknesses Of This Research and Future Studiesmentioning
confidence: 99%